Critérios delimitativos da atividade probatória de ofício no Processo Civil - Taricco, Adriana Delboni (2015)
The core of this work is the attempt to fix criteria that clarify the ex-officio judicial action in the evidence field. To do that, the philosophical theories of judicial activism and procedural guarantism are brought to discussion, taking into account the current situation of the evidentiary law in Brazil, always in an attempt to establish means to control the ex-officio evidence activity. It starts from the analysis of controversial issues in the field of judicial evidence, such as its concept, the definition of procedural truth, the delimitation of the nature of the rules on evidence, the rules concerning the application of the burden of proof, the role of atypical evidence in the legal system and the acceptance of illegal evidence through the application of proportionality. From this perspective, two philosophical theories, activism and guarantism, are considered, followed by the examination of the judge s figure in the new Civil Procedure Code. In the end, three ways to control the ex-officio evidence activity are fixed: the respect of the enjuizamento system, the judge s interpretation accountability and the viable, but still non-existent, figure of the investigating judge